Peluang Dan Ancaman Perdagangan Produk Kerajinan Dan Kebijakan Untuk Mengatasinya : Studi Kasus Indonesia dengan Singapura - Fitriyani; Daspar; Devi Yulia Sartika; Amellia Manda Putri; Nur Halimah (CV. ITTC INDONESIA, 2024)
Indonesian craft trade with Singapore has great potential to strengthen economic cooperation between the two countries. Indonesian handicrafts have a rich cultural heritage and craftsmanship, offering a variety of unique and high-quality products. As a dynamic global trade center, Singapore offers a wide and varied market for these handicrafts. Factors that influence handicraft trade between Indonesia and Singapore, such as trade policies, consumer preferences, and effective marketing strategies. Analyzing trade data and market trends makes it possible to consider the opportunities and challenges that arise in the development of handicraft trade between the two countries. Close cooperation between the government, economic actors and other stakeholders is the key to expanding Indonesia's craft trade with Singapore. Success in the competitive Singapore market also requires developing innovative marketing strategies, improving product quality and implementing high standards.